The enabling environment for upscaling integrated rice-shrimp systems in the Mekong River Delta of Vietnam - Nhuong Tran; Nhuong Tran; Khoi Dang; Lien Le; Thiep Do; Dat Ngo; Thinh Pham; Dung Le; Michael Akester (Frontiers in Sustainable Food Systems, 2025)
Integrated rice-shrimp (IRS) farming is commonly practiced in the Vietnamese Mekong Delta (VMD) region. When properly managed, IRS systems can provide farmers in saline-affected areas opportunities to produce food and generate income throughout the year. IRS systems are considered potential solutions to climate change adaptation and mitigation. This study employs a tailored Integrated Assessment Framework for Upscaling to investigate the feasibility and enabling conditions for successful scaling out of IRS systems in the VMD. Our findings indicates that IRS systems has already been widely adopted among the coastal provinces in the VMD, suggesting strong potential for scaling up to broader impacts. IRS systems offer notable environmental benefits and enhance economic resilience for local communities, though their social implications are less understood. Institutional conditions and local commitments strongly support the development and scaling of IRS systems, with stakeholders widely acknowledging their importance. Furthermore, extensive technical and economic data support the systems’ expansion. However, our study highlights several challenges that hinder the broader scaling of IRS systems, such as limited financial capacity, fragmented small-scale operations, and the weak role of farmer organizations. Market access, brand development, and value chain coordination remain underdeveloped. At the same time, irrigation infrastructure is poorly aligned with the dual requirements of rice and shrimp aquaculture production during the dry and rainy seasons. This study recommends that targeted financial mechanisms, strengthened farmer organizations, improved market coordination, and upgraded infrastructure are essential to fully realize the potential of IRS systems as sustainable and climate-resilient models in the VMD.